Tropes properties, objects, and mental causation - Ehring, Douglas, 1952- (Oxford : Oxford University Press, 2011)
Properties and objects are everywhere, but remain a philosophical mystery. Douglas Ehring argues that the idea of tropes - properties and relations understood as particulars - provides the best foundation for a metaphysical account of properties and objects. He develops and defends a new theory of trope nominalism.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Tropes (Philosophy)